Digitalization and job stress: exploring the mediating roles of job and personal aversion risk with gender as a moderator - Han, Shibo (Frontiers in Psychology, 2024)
Background: This time-lagged study delves into the impact of digitalization on job stress.Digitalization is defined as the incorporation of digital technologies into various aspects of work life, fundamentally transforming processes, interactions, and decision-making. Aim: The present research focuses on the mediating roles of job-related risk and personal risk, and the moderating effect of gender. We hypothesized that employees' aversion to risks, both in their professional and personal facets, mediates the relationship between the rapid digitalization of their work environment and the resultant job stress. Regarding gender as a moderator, recent research suggests that gender can influence the experience of workplace stress, with women often experiencing higher levels of stress than men in certain situations. This indicates that gender might also moderate the relationship between digital living, risk perception, and jobrelated stress. This approach allows for an examination of the ways in which digital technology adoption influences workplace stress, considering the temporally spaced data. Method:Conducted over three waves of data collection among 795 Chinese employees, the research utilizes Hayes's Model 8, adept at revealing the dynamics of digitalization's influence in the workplace and its effects on individual well-being.The study corroborates Hypothesis 1 by establishing a significant, albeit less pronounced, relationship between digital living and job stress. The findings also support Hypothesis 2 by demonstrating that both job risk and personal risk mediate this relationship.The study's results also validate Hypothesis 3, indicating that gender moderates the relationship between digital living, job risk, personal risk, and job stress. Finally, the significant interaction effects found in the study, particularly the stronger conditional negative effect of digital living on perceptions of job and personal risks for males, despite the absence of statistical significance failed to support Hypothesis 4. Implications: This study sheds light on the dynamics of job stress in the context of a digitalizing work environment. The results have important implications for designing workplace strategies and interventions that are sensitive to risk perceptions and gender differences in the digital era.